Albedo reduction for snow surfaces contaminated with soot aerosols: Comparison of experimental results and models. Issue 9 (2nd August 2022) - Lapuerta, Magín; González-Correa, Sofía; Ballesteros, Rosario; Cereceda-Balic, Francisco; Moosmüller, Hans
Abstract: Highly reflective snow surfaces are sensitive to contamination by light-absorbing particles. When such particles are deposited onto a snow surface, they reduce snow albedo, which leads to snow surface warming and accelerates snowmelt. To better understand and characterize the effects of light-absorbing particles on snow albedo, an experimental campaign was conducted in Cotos Port, Madrid Spain. A spectroradiometric system consisting of six spectroradiometers simultaneously measuring sun irradiance and snow radiance spectra over the range from 300 to 2500 nm was used. Measured snow albedo spectra were compared to modeled snow albedo spectra obtained with a novel snow radiative transfer model (OptiPar) developed by our research group. Comparison of these experimental and OptiPar-modeled results with results from open modeling software, such as SNICAR and snowTARTES, has demonstrated that the detailed consideration of soot aerosol shape and size is helpful for a good spectral albedo prediction and that OptiPar provides enough flexibility for optimal fitting. Graphical Abstract: UF0001